Copper(II) ion-exchanged montmorillonite as catalyst for the direct addition of N-H bond to CC triple bond - Joseph, Trissa; Shanbhag, G. V.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
An efficient synthesis of phenyl-(1-phenylethylidene)amine using copper-exchanged montmorillonite clay (Cu K-10) is demonstrated. The catalyst was characterized using UV-vis, XRD, BET surface area measurements, pyridine adsorption etc. The XRD and surface area measurement show that the structural characteristics of the support montmorillonite K-10 (K-10) are preserved after Cu exchange. The hydroamination of phenyl acetylene with aniline was carried out in toluene under reflux condition in N-2 atmosphere at 393 K. The reaction is highly regio-selective for only Markovnikoff's addition of an-tine to CC multiple bond and proceeded smoothly to completion. The reaction conditions were optimized to obtain complete conversion with respect to phenyl acetylene. Reaction data showed that the activity of the catalyst in hydroamination reaction is greater at higher reaction temperatures and nonpolar solvents and NZ pressure promotes the reaction drastically. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: alkyne; Aniline; Catalyst; hydroamination; K-10 montmorillonite clay; phenyl acetylene

Insight into the mechanism of selective mono-N-methylation of aniline on Cu1-xZnxFe2O4: a DRIFTS study - Vijayaraj, M.; Murugan, B.; Shubhangi B. Umbarkar; Hegde, S. G.; Gopinath, Chinnakonda S. (Journal of Molecular Catalysis A - Chemical, 2005)
Mechanism of selective mono-N-methylation of aniline with methanol on Cu1-xZn2FeO4 catalysts was investigated in detail. The interaction of reactants (aniline. methanol and methanol: aniline) and possible products (N-methylaniline (NMA), N,N-dimethylaniline (DMA) and o-toluidine (OT)) on catalysts surface was studied by temperature-dependent in situ FTIR spectroscopy. Methanol adsorbs dissociatively over catalysts surface at 373 K as methoxy species and is oxidized to formate species at high temperature through dioxymethylene and/or formaldehyde as a surface intermediate species. On the other hand, adsorption of aniline:methanol mixtures shows that methanol oxidation was completely hindered in the presence of aniline. Aniline adsorbs on the Lewis acid sites at <= 373 K with phenyl ring oriented in a perpendicular manner to the catalyst surfaced however, N-H bond scission occurs above 373 K. A comparison of adsorbed NMA and methanol: am line (3:1) mixture on Cu0.5Zn0.5Fe2O4 shows NMA forms from the reaction mixture at 473 K. However, maximum activity at 573 K in catalytic reaction studies suggests that desorption limits the methylation kinetics. FTIR study displays stable aniline and methyl species on ZnFe2O4 even at 573 K; however. no methyl species is detected on Cr0.95Zn0.05Fe2O4 at 473 K due to methanol reforming reaction and that limits the overall reaction and hence low catalytic activity. It is proposed that methanol is protonated on catalysts surface by the labile H+ due to N-H bond scission. Co-adsorption of acidity probes with aniline and methanol indicates that aniline methylation takes place at single acid-base site. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Aniline; Cu1-xZnxFe2O4; desorption limited; DRIFT; IR; Methanol; N-methylaniline; N-methylation; reaction mechanism

Selective synthesis of N,N-dimethyl aniline derivatives using dimethyl carbonate as a methylating agent and onium salt as a catalyst - Shivarkar, A. B.; Gupte, S. P.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A - Chemical, 2005)
N-Alkylation of anilines by dimethyl carbonate (DMC) catalyzed by onium salts has been demonstrated. The work presented here shows that a simple catalytic system consisting of onium salts in the presence of a small amount of water is extremely effective in enhancing the DMC mediated N-alkylation of anilines to dialkylated products. The effect of reaction conditions on the synthesis of N,N-dimethyl aniline (NNDMA) from aniline and DMC has been investigated. Under the optimized conditions highest yield of NNDMA obtained was 99.8%, which is the best reported for liquid phase N-alkylation of aniline using DMC. The role of water in enhancing the yield of NNDMA is explained and a reaction-networking scheme is constructed, which summarizes the chemistry behind liquid phase N-alkylation of anilines by DMC. The catalyst has been shown to recycle up to five times and at the end of fifth recycle almost 98% of NNDMA yields were obtained. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Aniline; Dimethyl carbonate; methylation; N; N-alkylation; N-dimethyl aniline; onium salts

On the ``Active spacer and stabilizer'' role of Zn in Cu1-xZnxFe2O4 in the selective mono-N-methylation of aniline: XPS and catalysis study - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Journal of Catalysis, 2006)
A systematic catalytic methylation study on ferrospinel materials led to the selective production of N-methylaniline (NMA) with Cu1-xZnxFe2O4. Aniline methylation was carried out on Cu1-xZnxFe2O4 with a feed composition of CH3OH:PhNH2:H2O = 3:1:1 at 513-633 K. NMA was formed selectively on all of the catalyst compositions, with trace amounts of secondary products under most of the conditions. Cu0.5Zn0.5Fe2O4 composition showed high catalytic activity and stability up to 100 h. Although the Cu2+ was responsible for methylation activity, Zn2+ enhanced the overall stability of the catalyst system. XPS investigations revealed that the degree of Cu2+ reduction decreased dramatically from x = 0.05/0.25 to 0.5/0.75 on spent catalysts. TPR studies indicated that the reducibility of Cu2+ decreased from fully reducible at 523 K with Cu-rich compositions to partially reducible at 573 K on x = 0.5. Stable activity observed on Cu0.5Zn0.5Fe2O4 can be attributed to the highly heterogeneous distribution of metal ions. This heterogeneous distribution indicates an important role of zinc, likely as an ``active spacer cum stabilizee' that hinders the reduction of active Cu2+ and contributes to prolonged activity. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Aniline; Ferrite; N-methylaniline; N-methylation; spacer; stabilizer; surface distribution; TPR; XPS

Natural kaolinitic clay: a remarkable catalyst for highly regioselective chlorination of arenes with Cl-2 or SO2Cl2 - Jayachandran, B.; Phukan, P.; Daniel, Thomas; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Natural kaolinitic clay containing transition metals such as Fe and Ti in its lattice has been found to exhibit unusual regioselectivity in the liquid-phase chlorination of arenes with either Cl-2 or SO2Cl2 as the chlorinating agent para-Chlorinated products are predominant for most of the substrates with an exceptional case of ortho-selectivity for the chlorination of aniline.
Keywords: Aniline; chlorination; chlorine; ortho-chloroaniline; sulfuryl chloride

Selective N-alkylation of aniline with methanol over a heteropolyacid on montmorillonite K10 - Nehate, Manoj; Bokade, Vijay V. (Applied Clay Science, 2009)
N-methylaniline is an industrially important product in the manufacture of paper, textile dyes, drugs, perfumes and explosives. The vapour phase alkylation of aniline with methanol forming N-methylaniline is advantageous over liquid phase alkylation. In present study, vapour phase methylation of aniline over dodecatungestophosphoric acid supported on K10 montmorillonite was systematically studied and optimization of process parameters was carried out. The 20% m/m DTPA/K10 was found to be optimum with 79% aniline conversion and 99% N-methylaniline selectivity. The reaction required milder operating conditions than reported for commercial catalysts. We also studied the feasibility of 20% m/m DTPA/K10 as a catalyst for the alkylation of aniline with other alcohols like ethanol, n-propanol, iso-propanol and n-butanol. The activity of 20% m/m DTPA/K10 decreased with increasing carbon number. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alkylation; Aniline; Heteropolyacid; montmorillonite K10; N-methylaniline

Synthesis of N-methylaniline by aniline alkylation with methanol over Sn-MFI molecular sieve - Niphadkar, P. S.; Joshi, P. N.; Gurav, H. R.; Deshpande, Suvarna S.; Bokade, Vijay V. (Catalysis Letters, 2009)
Sn-MFI molecular sieves (Tin silicalite-1) with SiO(2)/SnO(2) molar ratio of 50-150 were synthesized and characterized. Elemental analysis, XRD and DRUV-vis confirmed that prepared samples were of MFI zeolite structure and Sn was incorporated in MFI framework. Vapor phase methylation of aniline over Sn-MFI was systematically studied and optimizations of process parameters were carried out. Sn-MFI (SiO(2)/SnO(2) = 50) was found to be optimum catalyst with 55% aniline conversion and 60% N-methylaniline selectivity. At lower space velocity (higher contact time) of 1 h(-1), aniline conversion was found to be increased to 71% with reduction in N-methylaniline selectivity to 39% and increased in N,N-dimethylaniline selectivity to 58%. The reaction follows first order kinetics with respect to aniline having activation energy of 7.3 kcal/mol.
Keywords: Aniline; Lewis acid; Methanol; N-methylaniline; Sn-MFI

Influence of Al3+ insertion in the stannosilicate MFI framework on the catalytic performance in vapor phase aniline N-methylation - Niphadkar, P. S.; Joshi, P. N.; Deshpande, Suvarna S.; Bokade, Vijay V. (Applied Catalysis A-General, 2011)
Silica-based Sn-MFI, Al-MFI and Al-Sn-MFI molecular sieves were synthesized by hydrothermal crystallization of gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23 (TPA)(2)O:35H(2)O, where x ranges from 1/0 to 1/200 and y from 1/0 to 1/400. Keeping molar Si/(Al + Sn) = 50, the amount of tin and aluminum in hydrogel was varied (Sn:Al molar ratios = 1:0, 1:0.33, 1:1, 1:3, 0:1) to investigate the synergy between Lewis and Bronsted acid sites in acid catalyzed aniline N-methylation reaction. Catalyst characterization was done by Powder X-ray diffraction, DRUV-vis spectroscopy, temperature programmed ammonia desorption (TPAD) and FTIR spectroscopy. An increase in the Al3+ insertion in Sn-MFI framework resulted in the increase in the stronger acid sites. Al-Sn-MFI showed higher aniline conversion than their monometallic counterparts. A sample having B/L ratio in between 0.67 and 0.91 was found to be optimum for maximizing the NMA yield, indicating the existence synergistic properties of Al-Sn-MFI. Upon process parameter optimization, the optimum sample M50 [Si/Al = 50.2, Si/Sn = 93.8, Si/(Al + Sn) = 43.2] showed the maximum aniline conversion (67%) and NMA selectivity (81%) at reaction temperature = 220 degrees C, weight hourly space velocity (WHSV) = 3 h(-1), molar ratio (aniline to methanol) = 1:8 and TOS = 4 h. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-Sn-MFI; Aniline; Bronsted and Lewis acid; Methanol; N-methylaniline

Liquid-liquid equilibria of ternary mixtures containing Aniline plus Toluene plus water at elevated temperatures: measurements and correlation - Gaikwad, Shashank G.; Pathak, Abhishek A.; Mote, Dhananjay R.; Gogate, Parag R.; Singh, Shivani; Modhera, Bharat (Separation Science and Technology, 2023)
Liquid-liquid equilibrium (LLE) data for the ternary system, Aniline + Toluene + Water, was measured at different temperatures of 298.15 K, 313.15 K and 323.15 K under atmospheric pressure with the help of High-Performance Liquid Chromatography (HPLC) analysis and Karl-Fischer technique. The efficiency of Toluene to extract Aniline from aqueous phase was then quantified in terms of the distribution coefficient and separation factor based on the tie line data. The system showed very good separation ability quantified in terms of high values of distribution factor (average around 7) and separation factors (as high as 1000). The experimental tie line data was verified by Hand and Othmer-Tobias equations. The LLE data was also correlated using NRTL and UNIQUAC models and both of them were able to represent the behavior of the system accurately when tested against experimental results. Toluene has been demonstrated to be very efficient to extract Aniline from reaction mixture, which is typically a by-product in hydrogenation of nitrobenzene, a process commercially used to produce p-Aminophenol in industry.
Keywords: Aniline; LLE; NRTL; Tie line; Toluene; UNIQUAC